Morphological prediction of worker size discrimination and relative abundance of sympartic species of Pseudacteon (Dipt., Phoridae) parasitoids of the fire ant, Solenopsis saevissima (Hym., Formicidae) in Brazil - Fowler, H. G. [UNESP] (My University, 1997)
Patterns of attack for collected species of phorids are predicted using multivariate morphometrics of female Pseudacteon species and worker size distributions of parasitized fire ants, Solenopsis saevissima. The model assumes that there is a direct correlation between phorid size and the size range of the worker ant attacked, and presumes that worker sizes are a resource that is divided by sympatric phorid species to minimize joint parasitism. These results suggest that the community of sympatric Pseudacteon species on only one host species coexists by restricting the size of workers attacked, and secondarily by differing diel patterns of ovipositional activity. When we compared relative abundance of species of Pseudacteon with the size distribution of foragers of S. saevissima, our observed distribution did not differ significantly from our predicted relative abundance of females of Pseudacteon. The activity of Pseudacteon may be a factor determining forager size distributions.
Keywords: Pseudacteon; Solenopsis saevissima